Evaluation of long term oral administration of gamma irradiated tualang honey in specific pathogen free sprague-dawley rats - Mohd Ali, Nor Azeera (2015)
Gamma irradiated Tualang honey (GITH) is reported to have high antioxidant and free radical scavenging activities along with its anticancer, antibacterial, anti-inflammatory and wound healing properties. A detailed study to evaluate its long term oral administration is therefore, necessary. The study design was adapted from The Organisation for Economic Cooperation and Development (OECD) Guideline no. 452 with slight modifications. A total of 120 healthy male and female specific pathogen free (SPF) Sprague-Dawley rats (6±1 weeks old) were randomly divided into four groups (n=10-20 each) fed with different GITH doses [0 (Group I), 0.2 (Group II), 1.0 (Group III) and 2.0 g/kg body weight] (Group IV) daily for six months. Weekly body weight, mortality and morbidity, physical appearance and behavioural characteristics were recorded. After six months, blood sample of overnight fasted rats were analysed for haematology and clinical biochemistry parameters. Full gross necropsies were conducted followed by the determination of absolute and relative organ weights (ROW) were determined. Adrenal glands, kidneys and liver were then subjected to histological assessments. The study revealed that no morbidity and mortality were observed and no significant changes in body weight recorded between all groups. Group II (male and female) possessed significantly higher mean corpuscular haemoglobin concentrations (MCHC) when compared to Group IV (male) and other groups (female). Higher mean corpuscular haemoglobin (MCH) values were observed in female rats (Group II) when compared with other groups. Group IV (male) have lower blood urea nitrogen (BUN) when compared to Group I and II. Significantly lower alanine transaminase were observed in all GITH treated groups (male) in comparison with control group. No noticeable changes in gross appearance of rats internal organs were seen with no marked changes in absolute and ROW. Histological examinations revealed normal morphology of adrenal glands, kidneys and livers for all the rats. Histomorphometry analysis of adrenal glands revealed lower width of zona fasciculata regions in all GITH treated groups (male) and Group III (female) when compared to Group I. Dilatation of Bowman‟s space were observed in Group IV (male) in comparison to Group I and III. Significant variations of binucleated hepatocytes size in Group II and III as compared to Group I (male); and Group IV when compared to Group II and III (female) was observed. In conclusion, long term oral administration of GITH does not produce any detrimental effects in the body weight, physical and behavioural characteristics, as well as clinical laboratory analysis and histopathological parameters. Hence, overall findings suggested that GITH preserved the normal functions of adrenal glands, kidney and liver of SPF rats and may contribute to positive effects that warrant further evaluations.